1962
DOI: 10.1029/jz067i002p00681
|View full text |Cite
|
Sign up to set email alerts
|

An approach to the development of isohyetal maps for mountainous areas

Abstract: A technique was developed in which anomalies from precipitation‐elevation relationships were used in preparing isohyetal maps of Utah. October–April and May–September precipitation normals (averages for the 1921 to 1950 period) were computed for all available Utah precipitation records. The double‐mass analysis technique was used in the derivation of the October–April normals, and for this purpose the state was separated into eight climatic divisions. Relationships between precipitation and water equivalent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 2 publications
0
40
1
Order By: Relevance
“…24: (2004 are interpolated via a geostatistical method (kriging) and added to the regression field to account for any remaining spatial variation. Peck and Brown (1962) initially introduced the idea to add an interpolated field of residuals to the results of a functional relationship between climatic processes and topography to account better for both topography-related processes and any other remaining influences. The regionalization method has been termed 'AURELHY' ('Analysis Using the Relief for Hydrometeorology'; Benichou and Lebreton, 1987) and has been adopted by the French Weather Service (Météo France) as the standard for the preparation of climate maps.…”
Section: Regionalization Methodology For Climatic Data Including Relimentioning
confidence: 99%
“…24: (2004 are interpolated via a geostatistical method (kriging) and added to the regression field to account for any remaining spatial variation. Peck and Brown (1962) initially introduced the idea to add an interpolated field of residuals to the results of a functional relationship between climatic processes and topography to account better for both topography-related processes and any other remaining influences. The regionalization method has been termed 'AURELHY' ('Analysis Using the Relief for Hydrometeorology'; Benichou and Lebreton, 1987) and has been adopted by the French Weather Service (Météo France) as the standard for the preparation of climate maps.…”
Section: Regionalization Methodology For Climatic Data Including Relimentioning
confidence: 99%
“…Human-expert methods use human experience, expertise, and knowledge acquisition capabilities to infer climate patterns from meteorological regimes, physiographic features, biotic characteristics, and other information sources. They involve the manual preparation of climate maps (Reed & Kincer 1917, Peck & Brown 1962, often based on topographic analyses involving the correlation of point climate data with an array of topographic and synoptic parameters such as topographic position, slope, exposure, elevation, location of barriers, and wind speed and direction (Spreen 1947, Burns 1953, Stoeckeler 1963, Schermerhorn 1967, Hovecar & Martsolf 1971, Bootsma 1976, Houghton 1979, Basist et al 1994. Most of the 'official' precipitation maps for US states were created in the 1960s by federal agencies using humanexpert methods.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Previous studies have reported a simple proportionality relation between altitude and snow water equivalent (SWE) (e.g., Peck and Brown 1962). The relation is used to estimate the snow cover distribution.…”
Section: Introductionmentioning
confidence: 99%